Nivkh toponyms in the Amur-Sakhalin region of the Russian Far East - Gruzdeva, Ekaterina; Temina, Marina (THE ALTAIC SOCIETY OF KOREA, 2020)
This paper offers a survey of the indigenous toponymy of a limited geographical region covering the lower course of the river Amur and the island of Sakhalin in the Russian Far East. Place names of this region come from both indigenous and colonial languages and reveal several historical layers. The paper focuses on the toponyms which originate from the genetically isolated Nivkh (Ghilyak) language and examines the structural and semantic patterns of their derivation. The analysis of the material confirms that toponymy encodes important information about the ways in which indigenous peoples conceptualize the world and perceive their immediate ecological environment. Peer reviewed